Diagnostic pitfalls: a case of prostate cancer and rectal cancer accompanied by prostate cancer invasion of the rectum - Qiongxian Long; Ji Wu; Yong Peng; Xuqian Zhang; Xinya Liu; Huaping Chen (BMC, 2022)
Abstract Introduction Case of double primary cancer of the prostate and rectum is rare, prostate cancer involving the postoperative intestinal anastomotic mucosal tissue is even rarer. Case presentation We report a case of rectal cancer discovered 1 year after a diagnosis of prostate cancer and a tumour in the postoperative anastomotic intestinal mucosal tissue involving prostatic adenocarcinoma at 1 year after the diagnosis of rectal cancer. Due to the poor differentiation of both prostate and rectal cancers, there are some pitfalls in the diagnosis of intestinal mucosal lesions at an anastomosis. The lack of an accurate diagnosis of a tumour in anastomosis intestinal mucosal tissue will affect treatment and patient survival. Conclusions The pathologists should have a detailed understanding of the patient's medical history and carefully observe the histopathological morphology and, if necessary, immunohistochemistry or other techniques should be used to assist in the pathological diagnosis and avoid both misdiagnosis and missed diagnosis.